Evaluating a novel, integrative dashboard for health professionals' performance in managing deteriorating patients: a quality improvement project. Issue 4 (5th December 2022) - Alhmoud, Baneen; Melley, Daniel; Khan, Nadeem; Bonicci, Timothy; Patel, Riyaz; Banerjee, Amitava
Abstract : Background: The quality of recording and documentation of deteriorating patient management by health professionals has been challenged during the COVID-19 pandemic. Non-adherence to escalation and documentation guidelines increases risk of serious adverse events. Electronic health record (EHR)-integrated dashboards are auditing tools of patients' status and clinicians' performance, but neither the views nor the performance of health professionals have been assessed, relating to management of deteriorating patients. Objective: To develop and evaluate a real-time dashboard of deteriorating patients' assessment, referral and therapy. Settings: Five academic hospitals in the largest National Health Service (NHS) trust in the UK (Barts Health NHS Trust). Intervention: The dashboard was developed from EHR data to investigate patients with National Early Warning Score (NEWS2)>5, assessment, and escalation of deteriorating patients. We adopted the Plan, Do, Study, Act model and Standards for Quality Improvement Reporting Excellence framework to evaluate the dashboard. Design: Mixed methods: (1) virtual, face-to-face, interviews and (2) retrospective descriptive EHR data analysis. Results: We interviewed three nurses (two quality and safety and one informatics specialists). Participants perceived the dashboard as a facilitator for auditing NEWS2 recording and escalation of care to improve practice; (2) there is a need for guiding clinicians and adjusting data sources and metrics to enhance the functionality and usability. Data analysis (2019–2022) showed: (1) NEWS2 recording has gradually improved (May 2021–April 2022) from 64% to 83%;(2) referral and assessment completion increased (n: 170–6800 and 23–540, respectively). Conclusion: The dashboard is an effective real-time data-driven method for improving the quality of managing deteriorating patients. Integrating health systems, a wider analysis NEWS2 and escalation of care metrics, and clinicians' learning digital solutions will enhance functionality and experience to boost its value. There is a need to examine the generalisability of the dashboard through further validation and quality improvement studies.